The Current State of the Gamification in E-Learning: A literature Review of Literature Reviews - Rozman, Tomislav; Donath, Liliana (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The aim of this article is to present a systematic literature review of literature reviews (a meta-study) of gamification topics in e-learning with a purpose to present a high-level overview of the state of the development of the selected field. The systematic literature review of literature reviews (2010 - 2019) was performed. The academic papers (literature reviews) from several academic databases such as DOAJ, ScienceDirect, Google Sholar and WOS were examined and filtered for further study. The selected articles were analysed for sub-topics (e.g. the efficiency of gamification mechanisms) and summarized. In last 5 years, the research of gamification in various fields (mobile apps, e-health, human resource management, business development, e-learning) is getting traction and the number of research articles and systematic reviews of research articles is increasing. After filtering literature review articles, we have found out that only a handful of them – 19, which summarizes 2631 studies, are directly related to gamification in e-learning. This study shows that the following gamification mechanisms in e-learning proved themselves efficient in almost all underlying studies, but there is no broad consensus on terminology and how to group of different gamification related concepts. The research is limited to the following scholarly databases: DOAJ, Elsevier, Google Scholar, and WOS. We are aware that there is a possibility we missed some systematic literature reviews on this topic, which was indexed in other well-known databases or published using different terminology in the title or abstract. The article can serve as a starting point for the research for the scholars and especially post-graduate students who are getting familiar with the e-learning, gamification and performing systematic literature reviews. Also, developers of e-learning systems and course designers could benefit from this article by finding out which gamification mechanisms are most researched, most efficient and worth implementing. To our knowledge, this kind of meta-analysis of the literature reviews hasn’t been done in the field of gamification in e-learning for the year 2019.